The 5 A’s Approach to Promoting Nutrition Counseling in Primary Care - Farhad Mehrtash; JoAnn E. Manson (Journal of Primary Care & Community Health)
Poor dietary habits are a major contributor to chronic disease burden, yet nutrition counseling remains underutilized in primary care settings despite proven effectiveness. This article presents a novel adaptation of the 5 A’s framework (Assess, Advise, Agree, Assist, Arrange) titled ‘The 5 A’s Approach to Promoting Nutrition Counseling in Primary Care’, by incorporating validated assessment tools and evidence-based strategies to support implementation in clinical settings. To address practical challenges, implementation approaches are proposed including alternative delivery and payment models. The 5 A’s adaptation can be a tool used to address the critical need for standardized nutrition counseling in primary care.